Respuesta :
Rewrite the inner limit as
[tex]\displaystyle \lim_{n\to\infty} \prod_{k=1}^n \left(1 + \frac{(k+1)^p}{n^{p+1}}\right) \\\\ = \exp\left(\lim_{n\to\infty} \ln \prod_{k=1}^n \left(1 + \frac{(k+1)^p}{n^{p+1}}\right)\right) \\\\ = \exp\left(\lim_{n\to\infty} \sum_{k=1}^n \ln \left(1 + \frac{(k+1)^p}{n^{p+1}}\right)\right)[/tex]
For any x > 0, we have the useful bounds
[tex]x - x^2 \le \ln(1 + x) \le x[/tex]
so that
[tex]\displaystyle \sum_{k=1}^n \left(\frac{(k+1)^p}{n^{p+1}} - \frac{(k+1)^{2p}}{n^{2(p+1)}}\right) \le \sum_{k=1}^n \ln \left(1 + \frac{(k+1)^p}{n^{p+1}}\right) \le \sum_{k=1}^n \frac{(k+1)^p}{n^{p+1}}[/tex]
In the limit, we have
[tex]\displaystyle \lim_{n\to\infty} \sum_{k=1}^n \frac{(k+1)^p}{n^{p+1}} \\\\ = \lim_{n\to\infty} \frac1n \sum_{k=1}^n \left(\frac{k+1}n\right)^p \\\\ = \int_0^1 x^p \, dx = \frac1{p+1}[/tex]
and
[tex]\displaystyle \lim_{n\to\infty} \sum_{k=1}^n \frac{(k+1)^{2p}}{n^{2(p+1)}} \\\\ = \lim_{n\to\infty} \frac1n \times \frac1n \sum_{k=1}^n \left(\frac{k+1}n\right)^{2p} \\\\ = 0 \times \int_0^1 x^{2p} \, dx = 0[/tex]
Then by the squeeze theorem, the log sum converges to 1/(p + 1), so the infinite product converges to [tex]e^{\frac1{p+1}}[/tex], as suspected.
Finally,
[tex]\displaystyle \lim_{p\to\infty} \left(e^{\frac1{p+1}}\right)^{H_p} \\\\ = \exp\left(\lim_{p\to\infty} \frac{H_p}{p+1}\right) \\\\ = \exp\left(\lim_{p\to\infty} \frac{H_p-\ln(p) + \ln(p)}{p+1}\right) = e^0 = \boxed{1}[/tex]
since Hₙ - ln(n) converges to the Euler-Mascheroni constant γ.